Length change pattern of the medial structures of the knee and related reconstructions. Issue 9 (28th September 2020) - Olbrich, Arne; Herbst, Elmar; Domnick, Christoph; Glasbrenner, Johannes; Raschke, Michael J.; Frank, Andre; Herbort, Mirco; Kittl, Christoph
Introduction: Aim of the study was to investigate the length changes of the medial structures and related reconstructions. It was assumed that the three fibre sections (anterior/middle/posterior) of the superficial medial collateral ligament (sMCL) have different length change patterns, which cannot be imitated by current reconstructions. Hypotheses: The three fibre sections (anterior/middle/posterior) of the superficial medial collateral ligament (sMCL) cannot be imitated by current reconstructions. Methods: Measurements were made on eight cadaveric knees. The knee joints were clamped in a custom-made open chain extension structure. For this purpose, the portions of the quadriceps and the iliotibial tract were aligned according to their fibre direction and statically loaded using hanging weights. The respective tibial and femoral insertion points of the sMCL anterior/middle/posterior fibres were marked by small pins. Similarly, pins were inserted at the tibial and femoral attachment sites of the posterior oblique ligament (POL). In order to imitate the Lind reconstruction, a pin was additionally inserted on the tibial semitendinosus insertion site. Pin combinations accounting for the anterior/middle/posterior sMCL, the POL, and the Lind reconstruction were connected using a high resistant suture. Then the length change patterns were measured using a rotary encoder from 0-120° knee flexion. Statistical analysis was performed using 2-way repeated-measures ANOVA and a post-hoc Bonferroni correction (p <0.05). Results: The anterior and posterior fibres of the sMCL showed a reciprocal behaviour (p< 0.001). The anterior fibres showed a length reduction (2%) up to a flexion of 20°, followed by an elongation of 5% at 120° flexion, which means that the anterior fibres are tight in knee flexion. Conversely, the posterior fibres of the MCL showed an initial length reduction of 4% at 20° flexion. This was followed by an isometric range (20° - 80°) and a further length reduction of 8% in deep flexion (120°). Thus, the posterior fibres of the MCL were tight in extension. The three parts of the POL showed a constant reduction of 25% between 0° and 120°. The Lind reconstruction with the tibial pin at the semitendinosus insertion site showed similar length changes compared to the sMCL (n.s.). Furthermore, the Lind reconstruction was dependent on the femoral placement of the pins (p <.001). The tibial placement had no significant influence. Conclusion: The anterior portion of the sMCL was tight in flexion, whereas the posterior portion was tight in extension. This reciprocal behavior could not be imitated by a single point to point reconstruction. When surgically applying these reconstructions, special attention should be paid to the femoral insertion.